Plasma characteristics of two-step vacuum-arc discharge and its application for a coatings deposition - Timoshenko, A.I.; Taran, V.S.; Tereshin, V.I. (Вопросы атомной науки и техники, 2007)
Non-self-maintained gaseous discharge, where the vacuum-arc plasma gun is used as a source of supplementary charges, is characterized by a great currents and high values of ionization coefficient. This kind of discharge is well adapted for thermo-chemical treatment of products but still is not applied for a coatings deposition. In this paper we show the possibility of a-C:H films synthesis from a plasma of this discharge. The films obtained have a high transparence and good adhesion to metal and dielectric substrates. In addition, such parameters as temperature and density of electrons, ionization coefficient, plasma potential distribution and ion energy have been determined by probe methods for the plasma of non-self-maintained discharge in both: nitrogen and propane-butane mixture.